FREQUENCIES OF APPLICATION AND DILUTION OF NUTRIENT SOLUTION IN HYDROPONIC CULTIVATION OF ARUGULA - Santos, Jenyffer Da Silva Gomes; Da Silva, Alexsandro Oliveira; De Larcerda, Claudivan Feitosa; Costa, Raimundo Nonato Távora; Da Silva, Geronimo Ferreira; Putti, Fernando Ferrari [UNESP] (My University, 2022)
Fertilizer formulation, such as irrigation frequency, is fundamental for the success of cultivation, since the absorption of nutrients from the nutrient solution is a selective and dynamic process. Thus, the present experiment was conducted to evaluate the production of arugula in hydroponic cultivation subjected to different dilutions and frequencies of application of the nutrient solution. The experiments were carried out in a randomized block design with four replicates. A split-plot in a 5 x 2 factorial arrangement was used, which consisted of five dilutions based on the electrical conductivity of the nutrient solution (ECsol: 2.00 (control), 1.81, 1.62, 1.40, and 1.30 dS m-1) and two application frequencies (variable and fixed), totaling 40 experimental plots. Yield and growth variables, relative chlorophyll index and macronutrients were analyzed. Regarding shoot fresh mass, there was an increase with the ECsol, reaching a maximum of 15.52 and 8.40 g plant-1, with nutrient solutions of 1.77 dS m-1 (first cycle) and 1.88 dS m-1 (second cycle). Using only 90% of the recommended nutrient solution is the most appropriate from the commercial point of view, as it led to maximum potential in relation to yield, using a smaller number of inputs.
FREQUÊNCIA DE APLICAÇÃO E DILUIÇÃO DA SOLUÇÃO NUTRITIVA EM CULTIVO DE RÚCULA HIDROPÔNICA
Keywords: electrical conductivity; greenhouse; temperature sensor